Mycobacterium marinum Co-infection Masquerading as Treatment-Resistant Chromoblastomycosis: A Diagnostic and Therapeutic Challenge in Cutaneous Co-infection - Stefanus Soewito Sutanto; Ni Luh Putu Ratih Vibriyanti Karna; Herman Saputra; Robert Thiodorus (HM Publisher, 2026)
Background: Co-infection of chromoblastomycosis and Mycobacterium marinum (fish tank granuloma) within a single cutaneous lesion is exceptionally rare and presents a formidable diagnostic challenge owing to overlapping clinical and histopathologic features. The chronic verrucous or nodular morphology, predilection for distal extremities, and aquatic exposure history common to both conditions can lead to misdiagnosis, prolonged ineffective therapy, and patient morbidity. Case presentation: A 31-year-old Indonesian male with a fishkeeping hobby presented with a persistent erythematous plaque on the right middle finger, present since 2022, following a puncture injury sustained while collecting mosquito larvae and water fleas as fish food. He was initially diagnosed with chromoblastomycosis (Phialophora spp. on culture) in September 2023 and treated with itraconazole 200 mg daily and topical miconazole 2% for 48 weeks without resolution. Repeat biopsy in 2024 demonstrated negative periodic acid-Schiff and Ziehl-Neelsen stains but revealed non-caseating tuberculoid granulomas. Considering the patient's aquatic exposure, antifungal failure, and granulomatous histopathology, a diagnosis of fish tank granuloma due to M. marinum co-infection was established. Combination antimycobacterial therapy with rifampicin 600 mg and ethambutol 1500 mg daily produced clinical resolution at six-month follow-up. Conclusion: This case underscores the necessity of considering M. marinum in patients with antifungal-refractory chronic skin lesions and aquatic exposure, and highlights the diagnostic value of repeat histopathology with directed staining when initial therapy fails.